Fragment and vesicle structures in sonicated dispersions of dioctadecyldimethylammonium bromide - Feitosa, E.; Brown, W. (Amer Chemical Soc, 1997)
Dynamic light scattering has been used to investigate sonicated aqueous dispersions of dioctadecyldimethylammonium bromide (DODAB). The hydrodynamic radius (R-H) of the scattering particles and the mean scattering intensity (I) have been monitored as functions of the DODAB concentration and temperature (T). In the dilute regime, the relaxation time distribution of the sonicated dispersion of DODAB is bimodal with the slow mode dominating the distribution. The slow and fast modes are respectively characteristic of vesicles and bilayer fragments with R-H values of 22 and 8.5 nm (25 degrees C) and 20 and 6 nm (50 degrees C), respectively. The total scattered intensity initially decreased with temperature up to 45 degrees C (T-c), above which it was constant; identical behavior was observed for the slow mode intensity, but the fast mode intensity was constant with temperature change, showing that T-c is a property of the vesicles and not of the bilayer fragments. At T-c the slow vesicle mode becomes narrower whereas the fast fragment mode shows no change. on aging, the dispersion showed a slow transition from bimodal to a rather broad single-modal relaxation time distribution. The corresponding R-H was 33.8 nm when measured 10 months after preparation. These results suggest that aqueous sonicated dispersions of DODAB are metastable.